Perlembagaan Malaysia dalam era globalisasi: penerimapakaian undang-undang antarabangsa - Mohd Kamal, Mohd Hisham (Dewan Bahasa dan Pustaka, 2008)
This article discusses the extent to which the Federal Constitution allows for the application of international law in Malaysia. It argues that international treaties are applied after the treaty laws are enacted into Malaysian national statutes. It also finds that Malaysian courts adopt a few approaches in applying international customary law. Nevertheless, the application of international law must not affect fundamental elements of the constitution, especially Islam which is the religion of the Federation.